Quality of Residential Care for Children and Youth as Context, Process, and Outcome: A Scoping Review - Eriksson, Pia K.; Niemi, Minna; Kaittila, Anniina (Taylor & Francis, 2026)
A scoping literature review of peer-reviewed empirical studies explicitly exploring the quality of residential care (RC) delivery as a child welfare intervention was conducted. To map the features of quality addressed in the included 14 articles, we scrutinized different stakeholder perspectives and used the Donabedian framework of context, process, and outcome. The concept of quality is scarcely used and defined in original studies. Further, nearly all the reviewed studies focus on only one or a few quality dimensions or domains. Most emphasized was the interpersonal dimension and setting within the process domain; the technical dimension in the process as the domain of outcomes receive the least attention. Emphasis is more on how RC should be offered, and less on what it entails and what the expected outcomes are.